A high strength and high electrical conductivity CuCrZr alloy prepared by aging and subsequent cryorolling. (August 2021) - Li, G.Y.; Li, S.Y.; Li, L.; Zhang, D.T.; Wang, J.D.; Tong, Y.X.
Abstract: In the present study, high strength and high electrical conductivity Cu-0.65Cr-0.07Zr (wt.%) was prepared by aging and subsequent cryorolling. The influence of processing on microstructure and properties of alloy were investigated. After aging, the fine and uniformly dispersed nano-precipitates appeared in the matrix. The cryorolled sample was characterized by a finer microstructure than the sample rolled at room temperature. The desired balance between the tensile strength of 712 MPa and electrical conductivity of 70.2% was obtained in the sample aged and cryorolled for 90% reduction. The combination of aging and subsequent cryorolling is effective in optimizing mechanical strength and electrical conductivity of CuCrZr alloy due to grain refinement, precipitation and twinning. Highlights: After aging, fine and uniformly dispersed nano-precipitates appear in matrix. The cryorolled sample shows much finer microstructure than the sample rolled at room temperature. Aging and subsequent cryorolling is effective in optimizing strength and electrical conductivity.